Armed Batavians Use and Significance of Weaponry and Horse Gear from Non-military Contexts in the Rhine Delta (50 BC to AD 450) - Nicolay, Johan (Amsterdam Archaeological Studies, 2007)
Using a life-cycle model for Roman soldiers, Johan Nicolay interprets the large quantity of first-century finds as personal memorabilia brought home by ex-soldiers as a reminder of their twenty-five years of service and a symbol of their newly-acquired veteran status. Underpinning Nicolay's research is an extensive inventory of militaria from urban centers, rural settlements, rivers, and graves-presented in nearly one hundred individual color plates. Introducing a considerable body of unpublished data, as well as offering a perspective on daily life in the northern frontier of the Roman Empire, this volume is a valuable addition to Roman military and material history.